ANALISIS UNSUR INTRINSIK DAN NILAI PENDIDIKAN KARAKTER DALAM CERPEN “KISAH TIGA KERAJAAN LAMPAU” KARYA DAVID VICTOR - Salman Paris; Rika Laelasari; Yusep Ahmadi F (Parole (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2018)
This study analyzes the intrinsic elements and values of character education in the short story "The Story of Three Kingdoms" by David Victor. The reason the author chose this short story because the story is interesting, short, easy to understand and only focused on a conflict. This study aims to describe the intrinsic element and the value of character education. The findings show there are intrinsic elements that build the short story, among others: theme, plot, setting, character and characterization, the point of view, mandate, plot, and character are made with clear parts from preliminary to ending. It can be said as a short story that fills the whole structure. In addition found the values of character education in this short story such as creative, cooperation, love peace, caring, hard work, friendly and communicative. This short story can be used as learning material for prose literature in high school.